1994
DOI: 10.1182/blood.v83.3.691.691
|View full text |Cite
|
Sign up to set email alerts
|

Glycocalicin: a new assay--the normal plasma levels and its potential usefulness in selected diseases

Abstract: Platelet glycocalicin (GC) is the extramembranous portion of GPIb alpha that can be rapidly cleaved by enzymes such as calpain, plasmin, trypsin, elastase, etc. Quantitative cleavage will ultimately result in an acquired Bernard-Soulier-like bleeding disorder, and circulating GC may act as a potential inhibitor of platelet adhesion. We have developed and standardized a new enzyme-linked immunosorbent assay (ELISA), which uses two monoclonal antibodies (mAbs), both of which bind to the amino-terminal 45-kD frag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
49
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(53 citation statements)
references
References 51 publications
4
49
0
Order By: Relevance
“…Although platelet counts decreased immediately after surgery and gradually increased over time, no change in the GC concentration was observed. Previously, GC has been shown to be a marker for platelet turnover and is thought to be enzymatically cleaved from the platelet during destruction (Coller et al, 1984;Steinberg et al, 1987;Beer et al, 1994). It is probable that the follow-up of the patients in this study was too short to detect an increment in GC concentration because the newly produced platelets were still viable at the end of the follow-up.…”
Section: Discussionmentioning
confidence: 78%
“…Although platelet counts decreased immediately after surgery and gradually increased over time, no change in the GC concentration was observed. Previously, GC has been shown to be a marker for platelet turnover and is thought to be enzymatically cleaved from the platelet during destruction (Coller et al, 1984;Steinberg et al, 1987;Beer et al, 1994). It is probable that the follow-up of the patients in this study was too short to detect an increment in GC concentration because the newly produced platelets were still viable at the end of the follow-up.…”
Section: Discussionmentioning
confidence: 78%
“…If the observed correlation between GC levels in the fetuses and mothers was not merely by chance, it may indicate a placental transfer of GC. However, this is rather unlikely for a protein with a MW of 135 kDa (Beer et al, 1994) unless there is an active transport system, as has been observed for IgG.…”
Section: Discussionmentioning
confidence: 93%
“…It is unclear, however, whether these larger platelets are responsible for platelet hyperreactivity. Another marker, plasma glycocalicin, the extramembranous portion of GPIb, has recently been investigated by an enzymeimmunoassay [69]. It may have the potential for use as a marker of platelet damage [69].…”
Section: Other Platelet Markersmentioning
confidence: 99%